The balance between gyrase and topoisomerase I activities determines levels of supercoiling, nucleoid compaction, and viability in bacteria - García-López, Míriam; Megias, Diego; Ferrándiz, María-José; de la Campa, Adela G. (Frontiers in Microbiology, 2023)
Two enzymes are responsible for maintaining supercoiling in the human pathogen Streptococcus pneumoniae, gyrase (GyrA2GyrB2) and topoisomerase I. To attain diverse levels of topoisomerase I (TopoI, encoded by topA), two isogenic strains derived from wild-type R6 were constructed: PZntopA, carrying an ectopic topA copy under the control of the ZnSO4-regulated PZn promoter and its derivative topAPZntopA, which carries a topA deletion at its native chromosomal location. We estimated the number of TopoI and GyrA molecules per cell by using Western-blot and CFUs counting, and correlated these values with supercoiling levels. Supercoiling was estimated in two ways. We used classical 2D-agarose gel electrophoresis of plasmid topoisomers to determine supercoiling density (σ) and we measured compaction of nucleoids for the first time using super-resolution confocal microscopy. Notably, we observed a good correlation between both supercoiling calculations. In R6, with σ = 0.057, the average number of GyrA molecules per cell (2184) was higher than that of TopoI (1432), being the GyrA:TopoI proportion of 1:0.65. In topAPZntopA, the number of TopoI molecules depended, as expected, on ZnSO4 concentration in the culture media, being the proportions of GyrA:TopoI molecules in 75, 150, and 300 µM ZnSO4 of 1:0.43, 1:0.47, and 1:0.63, respectively, which allowed normal supercoiling and growth. However, in the absence of ZnSO4, a higher GyrA:TopoI ratio (1:0.09) caused hyper-supercoiling (σ = 0.086) and lethality. Likewise, growth of ΔtopAPZntopA in the absence of ZnSO4 was restored when gyrase was inhibited with novobiocin, coincidentally with the resolution of hyper-supercoiling (σ change from 0.080 to 0.068). Given that TopoI is a monomer and two molecules of GyrA are present in the gyrase heterotetramer, the gyrase:TopoI enzymes proportion would be 1:1.30 (wild type R6) or of 1:1.260.86 (topAPZntopA under viable conditions). Higher proportions, such as 1:0.18 observed in topAPZntopA in the absence of ZnSO4 yielded to hyper-supercoiling and lethality. These results support a role of the equilibrium between gyrase and TopoI activities in supercoiling maintenance, nucleoid compaction and viability. Results gave new light on the mechanism of action of topoisomerase-targeting antibiotics, opening the wave for using combination therapies.